Commentary on “Failer et al. (2022) Developmental endothelial locus-1 protects from hypertension-induced cardiovascular remodeling via immunomodulation” J Clin Invest 2022 (https://doi.org/10.1172/JCI126155) - Markus Sperandio (Pflügers Archiv - European Journal of Physiology, 2022)
Lung cancer histological subtypes include lung adenocarcinoma (LUAD) and small cell lung cancer (SCLC). Although usually distinct, rare combined LUAD/SCLC tumors occur, and LUAD can transform into SCLC as a mechanism of resistance to targeted therapies, particularly in EGFR-Mutant LUADs with RB1/TP53 inactivation. Although PRC2 complex expression increases during this transformation, its functional role remains unclear. Using CRISPR-based autochthonous immunocompetent GEMMs, we found that inactivation of EED, the core PRC2 scaffolding subunit, impaired SCLC tumorigenesis and promoted LUAD histological identity likely through a NEUROD1-positive intermediate state. Mechanistically, EED loss derepressed bivalent genes co-marked by H3K27me3 and H3K4me3, including LUAD oncogenic RAS, PI3K, and MAPK pathway genes and NEUROD1. These same LUAD oncogenic signaling genes were bivalently repressed in human SCLC patient-derived xenografts, suggesting a conserved PRC2-dependent mechanism that represses LUAD oncogenic signaling and thereby supports the SCLC neuroendocrine identity. In a complementary EGFR-Mutant LUAD GEMM with Rb1 and Trp53 inactivation, EED inactivation at tumor initiation prevented the emergence of SCLC histology after EGFR oncogene withdrawal and redirected recurrent tumors toward mucinous LUAD states with reduced spontaneous metastasis. These findings identify PRC2/EED as a regulator of SCLC neuroendocrine identity and nominate pharmacologic EED inhibition for future investigation in therapy-associated LUAD-to-SCLC transformation.